Glutamine synthetase stabilizes the binding of GlnR to nitrogen fixation gene operators. (11th February 2017) - Fernandes, Gabriela de C.; Hauf, Ksenia; Sant'Anna, Fernando H.; Forchhammer, Karl; Passaglia, Luciane M. P.
Abstract : Biological nitrogen fixation (BNF) is a high energy demanding process carried out by diazotrophic microorganisms that supply combined nitrogen to the biosphere. The genes related to BNF are strictly regulated, but these mechanisms are poorly understood in gram‐positive bacteria. The transcription factor GlnR was proposed to regulate nitrogen fixation‐related genes based on Paenibacillus comparative genomics. In order to validate this proposal, we investigated BNF regulatory sequences in Paenibacillus riograndensis SBR5 T genome. We identified GlnR‐binding sites flanking σ A ‐binding sites upstream from BNF‐related genes. GlnR binding to these sites was demonstrated by surface plasmon resonance spectroscopy. GlnR‐DNA affinity is greatly enhanced when GlnR is in complex with feedback‐inhibited (glutamine‐occupied) glutamine synthetase (GS). GlnR–GS complex formation is also modulated by ATP and AMP. Thereby, gene repression exerted by the GlnR‐GS complex is coupled with nitrogen (glutamine levels) and energetic status (ATP and AMP). Finally, we propose a DNA‐looping model based on multiple operator sites that represents a strong and strict regulation for these genes. Abstract : The biological nitrogen fixation (BNF) is strictly regulated at the transcriptional level, but these elements in gram‐positive bacteria are poorly characterized. GlnR, known as a general repressor in nitrogen metabolism, also regulates BNF‐related genes. GlnR interaction with the feedback‐inhibited glutamine synthetase (FBI‐GS) stabilizes its DNA‐binding function. Multiple operators at the BNF promoter sustain strong and strict repression.